The Effect of Effleurage Massage on Reducing Back Pain in Third-Trimester Pregnant Women at TPMB Lina Contesa - Bella Riska Ayu; Junie Harista; Erina Chintya Angraini (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Lower back pain is one of the most common discomforts experienced by third-trimester pregnant women due to increased uterine size, postural changes, and musculoskeletal strain. Complementary therapies such as effleurage massage offer a non-pharmacological, safe, and easily applicable technique to reduce pregnancy-related pain. This study aimed to examine the effect of effleurage massage on reducing lower back pain among third-trimester pregnant women at TPMB Lina Contesa. This research employed a quasi-experimental one-group pretest–posttest design. The study was conducted from October to November 2025 involving 32 third-trimester pregnant women selected through purposive sampling. Pain intensity was measured before and after the intervention using the Visual Analog Scale (VAS). Effleurage massage was administered for 15–20 minutes on the lower back region following standard midwifery procedures. Data were analyzed using the Wilcoxon test. The findings showed a significant reduction in lower back pain intensity after the intervention (p < 0.001). The proportion of respondents in the moderate-pain category decreased from 65.6% to 21.9%, while those in the mild-pain category increased from 34.4% to 78.1%. The mean VAS score dropped from 5.81 ± 1.12 before intervention to 2.47 ± 1.03 after effleurage massage. Effleurage massage is effective in reducing lower back pain among third-trimester pregnant women and can be recommended as a complementary therapy in midwifery care to improve maternal comfort.